Representasi Feminisme Liberal Pada Tokoh Sophie Hatter Dalam Anime Howl’s Moving Castle Karya Miyazaki Hayao - Cheryl Teendrata; Kadek Eva Krishna Adnyani; Yeni Rahman (STKIP AGAMA HINDU SINGARAJA, 2023)
This research aims to describe the representation of liberal feminism in the anime Howl's Moving Castle directed by Miyazaki Hayao. This type of research was using descriptive qualitative analysis method. The theory of Roland Barthes' semiotics and liberal feminism ideology were used in this research. The data that has been collected will be analyzed with the concept of two orders of signification in semiotics that includes denotation (explicit), connotation (implicit), and myth. The results found in the research show that the main character Sophie Hatter reflects a sign of liberal feminism. Various signs of liberal feminism appear through Sophie Hatter's character designs which include self-confidence, toughness, and courage. In the context of characterization analysis about Sophie Hatter is shown through the stages of her life's adventure can form an identity to expressing herself freely. In the other hand, the myth in the anime Howl''s Moving Castle shows the contradiction between ideology of liberal feminism and Japanese society’s point of view towards the freedom of life for women. The connection between Sophie Hatter and liberal feminism refers to women's rights in the sense that they are equal as same as the men.